The TESTING THE BENEISH M-SCORE MODEL IN DETECTING FRAUDULENT FINANCIAL STATEMENTS WITH THE HEXAGON FRAUD THEORY: FRAUD - Devy Diana Dinda Bestari; Triyanto, Eko (SUBSTANSI, 2025)
Research objective: This study aims to test the Beneish M-Score model in detecting fraudulent financial statements with the Fraud Hexagon theory. Method: This research is quantitative, with purposive sampling used to collect samples from secondary data from the financial reports of construction companies for the 2022-2024 period. Data analysis methods used descriptive analysis and logistic regression analysis using IBM SPSS 25 software. Research findings: The research findings show that pressure, opportunity, rationalization, capability, arrogance, and collusion partially and simultaneously do not influence fraudulent financial statements. Practical implication: Companies need to consider other factors in preventing fraud, such as corporate governance and internal control, especially the effectiveness of audits as actors in detecting potential fraudulent acts. Keywords: Finance; Fraud; Hexagon; M-Score; Ratio.